2017
DOI: 10.1038/s41598-017-01698-0
|View full text |Cite
|
Sign up to set email alerts
|

A short artificial antimicrobial peptide shows potential to prevent or treat bone infections

Abstract: Infection of bone is a severe complication due to the variety of bacteria causing it, their resistance against classical antibiotics, the formation of a biofilm and the difficulty to eradicate it. Antimicrobial peptides (AMPs) are naturally occurring peptides and promising candidates for treatment of joint infections. This study aimed to analyze the effect of short artificial peptides derived from an optimized library regarding (1) antimicrobial effect on different bacterial species, (2) efficacy on biofilms, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Bormann et al reported high antimicrobial potency of some AMPs against bacteria both incorporated in a biofilm or internalized into cells with no harm to human osteoblasts [ 113 ]. Furthermore, Hui Li et al demonstrated that KR-12 - a fragment of human antimicrobial peptide cathelicidin LL-37 improves the osteogenic differentiation of human bone marrow mesenchymal stem cells via stimulating BMP/SMAD signaling [ 114 ].…”
Section: Applications Of Amps In Some Infectious Diseasesmentioning
confidence: 99%
“…Bormann et al reported high antimicrobial potency of some AMPs against bacteria both incorporated in a biofilm or internalized into cells with no harm to human osteoblasts [ 113 ]. Furthermore, Hui Li et al demonstrated that KR-12 - a fragment of human antimicrobial peptide cathelicidin LL-37 improves the osteogenic differentiation of human bone marrow mesenchymal stem cells via stimulating BMP/SMAD signaling [ 114 ].…”
Section: Applications Of Amps In Some Infectious Diseasesmentioning
confidence: 99%
“…In implant-associated infection several factors are involved such as surgical procedure, microorganisms, host, type of the implant and antimicrobial prophylaxis [ 30 , 31 ]. The predominant microbial agent isolated from implant-associated infection is Staphylococcus aureus (30%), followed by coagulase-negative staphylococci (22%), but Gram-negative bacteria, enterococci, streptococci and other species may be isolated [ 32 , 33 ]. In conformity with current knowledge, biofilm formation presumably is the most critical pathogenic event in implant-associated infection.…”
Section: Implant-associated Infectionsmentioning
confidence: 99%
“…The implants protect the microorganisms from the host immune system and systemic antibiotics [ 30 ]. Bacterial adhesion to the implant surface—and colonization of the tissue surrounding the implant secretion of exopolysaccharides, aggregation in a slime layer and further differentiation and biofilm formation—are the most significant steps in implant infection [ 2 , 32 , 33 , 34 , 35 ]. Bacterial adhesion to the surfaces is generally nonspecific and it is produced by unspecific forces, namely, van der Wall, acid base or electrostatic interaction [ 36 ].…”
Section: Implant-associated Infectionsmentioning
confidence: 99%
See 2 more Smart Citations